Geographic correlation between deprivation and risk of meningococcal disease: an ecological study - Lake Iain R; Willocks Lorna J; Williams Christopher J; Hunter Paul R (BMC, 2004)
Abstract Background Meningitis caused by Neisseria meningitidis is a serious infection which is most common in young children and adolescents. This study investigated the relationships between the incidence and age distribution of meningococcal disease, and socioeconomic environment. Methods An ecological design was used, including mapping using a Geographical Information System (GIS) at census ward level. Results Incidence of meningococcal disease was highest in the most deprived wards, with a relative risk of 1.97 (1.55 - 2.51). Mapping revealed geographical coincidence of deprivation and meningococcal disease, particularly in urban areas. Two-thirds of the increased incidence was due to cases in the under fives. Conclusions The results suggest that area deprivation is a risk factor for meningococcal disease, and that its effects are seen most in young children.